Neoadjuvant chemotherapy followed by minimally invasive esophagectomy is safe and feasible for treatment of esophageal squamous cell carcinoma. Issue 2 (10th January 2018) - Ma, Shaohua; Yan, Tiansheng; Liu, Dandan; Wang, Keyi; Wang, Jingdi; Song, Jintao; Wang, Tong; He, Wei; Bai, Jie; Jin, Liang; Chen, Xiaoxin
Abstract : Background: The advantage of neoadjuvant chemotherapy (NAC) followed by open esophagectomy for treatment of esophageal squamous cell carcinoma has been widely recognized. However, the safety and feasibility of NAC for patients receiving minimally invasive esophagectomy (MIE) remain controversial. The purpose of this study was to evaluate the potential impact of prior neoadjuvant chemotherapy on the clinical outcome of MIE by comparing two groups of patients, MIE alone and NAC plus MIE. Methods: From May 2013 to July 2017, 124 patients with esophageal squamous cell carcinoma underwent MIE in our department, with 57 cases receiving NAC plus MIE and 67 cases receiving MIE alone. Perioperative parameters and short‐term postoperative survival were compared between these two groups to evaluate the safety and feasibility of NAC given before MIE. Results: The group with NAC plus MIE had slightly longer operating time, more blood loss, higher morbidity, increased chance of surgical intensive care unit stay, and longer surgical intensive care unit stay time than the group with MIE alone. However, there was no statistically significant difference between these two groups ( P > 0.05). The number of lymph nodes harvested was similar in the two groups without significant difference ( P > 0.05). The overall survival was not significantly different between these two groups either ( P > 0.05), although before surgery the clinical stage of the group with NAC plus MIE was more advanced than the group with MIE alone. Conclusions: NAC followed by MIE is safe and feasible for treatment of esophageal squamous cell carcinoma. NAC does not negatively impact the therapeutic outcome of MIE.